Sport psychology : - Cox, Richard H. (McGraw-Hill, 2007)
This introduction to sport and exercise psychology shows how principles supported by current scientific research can be used by physical educators, coaches, and athletes in everyday situations. It also addresses practical issues, such as dealing with anxiety, arousal, and stress; developing coping, relaxation, and energizing strategies; understanding the effects of an audience on human performance; building team cohesion; and preventing burnout.